Preservation of alfalfa hay with a microbial inoculant - Taylor, R.K.; Mahanna, W.C.; Blasi, Dale A.; Maxwell, Thomas Mark; Shroyer, James P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eleven large, round, alfalfa bales were treated with Pioneer® Brand 1155 Alfalfa Hay Inoculant and nine bales were untreated. The initial baling moistures were 14.1% (low) or 17.6% (medium). No significant differences were found in dry matter recovery or changes in acid detergent fiber, neutral detergent fiber, and acid detergent insoluble nitrogen levels during the 2-month storage period. Average temperature was highest in the medium moisture bales, but was not high enough to cause heat damage. The microbial inoculant did not improve preservation or quality of the alfalfa hay at the baling moistures used in this study.
Keywords: Beef; Alfalfa; Hay preservation; Round bales; Inoculant